2021
DOI: 10.1177/13591053211014586
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress in medicine: An ethical analysis

Abstract: Moral distress is a negative emotional response that occurs when physicians know the morally correct action but are prevented from taking it because of internal or external constraints. Moral distress undermines a physician’s ethical integrity, leading to anger, poor job satisfaction, reduced quality of care and burnout. Scarce literature exists on the ethical aspects of moral distress in medicine. We conducted an ethical analysis of moral distress as experienced by physicians and analysed it from the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 82 publications
0
29
0
Order By: Relevance
“…O'Neal et al ( 17 ) found 66.5% of surveyed HCPs felt moral distress related to conflicts between institutional constraints and what they believed was right during the pandemic. Similar moral dilemmas have been suggested for physicians who may be experiencing tensions between physicians' fidelity to best medical practices, their Hippocratic Oath, and managing scarce resources ( 18 ). Factors and experiences which have been found to cause moral distress during COVID-19 include uncertainty and lack of knowledge, fear of exposure, intra-professional tensions and miscommunications, policies that prevent or impede care, practicing within crisis standards of care, new roles/tasks and broken routines, and dealing with medical resource scarcity ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 65%
“…O'Neal et al ( 17 ) found 66.5% of surveyed HCPs felt moral distress related to conflicts between institutional constraints and what they believed was right during the pandemic. Similar moral dilemmas have been suggested for physicians who may be experiencing tensions between physicians' fidelity to best medical practices, their Hippocratic Oath, and managing scarce resources ( 18 ). Factors and experiences which have been found to cause moral distress during COVID-19 include uncertainty and lack of knowledge, fear of exposure, intra-professional tensions and miscommunications, policies that prevent or impede care, practicing within crisis standards of care, new roles/tasks and broken routines, and dealing with medical resource scarcity ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 65%
“…It is argued that the primary goal in addressing moral distress is to address the moral or ethical issues that cause the distress ( 18 ). In the healthcare sector, ethics training has been shown to help reduce moral distress ( 12 ). In the veterinary sector, understanding and application of ethics is identified as a key day-1 competency by the World Organisation for Animal Health (OIE) ( 19 ), and accrediting bodies including the Royal College of Veterinary Surgeons (UK) ( 20 ), the European Association of Establishments for Veterinary Education (Europe) ( 21 ), and the North American Veterinary Medical Education Consortium ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Millar argued that “beyond early career training, there is also an increasing need to support the development of a broader set of ethical reflection skills within the veterinary profession that goes beyond just raising awareness and knowledge acquisition” ( 26 ). Organizational support is critical in facilitating positive coping strategies ( 12 ). Organizational support includes creating a culture of ethical reflection and discussion, stimulating open dialogue among colleagues and with patients, and investing in medical ethics education for staff.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations